FORMULASI UBI JALAR, TAHU, DAN TERI KERING SEBAGAI PMT BALITA STUNTING USIA 1 – 3 TAHUN - Putri, Atika Setyowati; Fajar, Ibnu; I Dewa Nyoman, Supariasa (Journal of Local Therapy, 2022)
The proportion of malnutrition, undernutrition, and stunted in children under five is still a challenge for the government and the people of Indonesia. Deficit in energy consumption, macro and micro nutrients is said to be one of the causes of disrupted growth and development. A balanced intake of carbohydrates, proteins and fats is needed in the formation of body tissues, brain development and body resistance. Minerals Calcium (Ca), Phosphorus (P), and Potassium (K) are needed for growth, health and bone density. Sweet potatoes, tofu and dried anchovies are food ingredients that are rich in K, P and Ca minerals and can be developed into a supplementary feeding for toddlers that are rich with energy and nutrient sources. The purpose of this study was to determine the effect of the formulation of sweet potato, tofu, and dried anchovies on the quality of energy, nutrients, protein quality and organoleptic quality as supplementary feeding for toddlers. This type of research is a laboratory experimental study using 3 levels of treatments with different proportions of sweet potato, tofu and dried anchovies. The results of statistical analysis showed that there was no significant effect on the organoleptic quality of color, aroma and texture (p = 0.13; p = 0.74; p = 0.29), and there was a significant effect on the organoleptic quality of taste (p = 0.04). The best treatment level was P3 with an energy value of 144.2 Kcal, protein 5.1 grams, fat 7.8 grams, carbohydrates 13.9 grams, fiber 1.3 grams, calcium 58.6 milligrams, phosphorus 68.6 milligrams, potassium 135.2 milligrams